Air pollution and plasma amyloid beta in a cohort of older adults: Evidence from the Ginkgo Evaluation of Memory study. (February 2023) - Hajat, Anjum; Park, Christina; Adam, Claire; Fitzpatrick, Annette L.; Ilango, Sindana D.; Leary, Cindy; Libby, Tanya; Lopez, Oscar; Semmens, Erin O.; Kaufman, Joel D.
Highlights: Mechanisms of air pollution and Alzheimer's disease and related dementias not clear. Association between air pollution and plasma amyloid beta has not been studied. Positive association between air pollution and amyloid beta. Air pollution is modifiable target for dementia prevention. Abstract: Air pollution has been linked to Alzheimer's disease and related dementias (ADRD), but the mechanisms connecting air pollution to ADRD have not been firmly established. Air pollution may cause oxidative stress and neuroinflammation and contribute to the deposition of amyloid beta (Aβ) in the brain. We examined the association between fine particulate matter<2.5 μm in diameter (PM2.5 ), particulate matter<10 μm in diameter (PM10 ), nitrogen dioxide (NO2 ), and plasma based measures of Aβ1-40, Aβ1-42 and Aβ1-42/Aβ1-40 using data from 3044 dementia-free participants of the Ginkgo Evaluation of Memory Study (GEMS). Air pollution exposures were estimated at residential addresses that incorporated address histories dating back to 1980, resulting in one-, five-, 10- and 20- year exposure averages. Aβ was measured at baseline (2000–2002) and then again at the end of the study (2007–2008) allowing for linear regression models to assess cross-sectional associations and linear random effects models to evaluate repeated measures. After adjustment for socio-demographic and behavioral covariates, we found small positive associations between each air pollutant and Aβ1-40 but no association with Aβ1-42 or the ratio measures in cross sectional analysis. In repeat measures analysis, we found larger positive associations between each air pollutant and all three outcomes. We observed a 4.43% (95% CI 3.26%, 5.60%) higher Aβ1-40 level, 9.73% (6.20%, 13.38%) higher Aβ1-42 and 1.57% (95% CI: 0.94%, 2.20%) higher Aβ1-42/Aβ1-40 ratio associated with a 2 µg/m 3 higher 20-year average PM2.5 . Associations with other air pollutants were similar. Our study contributes to the broader evidence base on air pollution and ADRD biomarkers by evaluating longer air pollution exposure averaging periods to better mimic disease progression and provides a modifiable target for ADRD prevention.